Perfil das interações medicamentosas com a terapia antirretroviral em pessoas vivendo com HIV em um serviço de referência de Belo Horizonte - 2015-2016 - Betânia Maira Pontelo (2017)
HIV infection may be considered a chronic condition for people living with HIV (PLWH) with access to antiretrovirals (ARVs) and this has effectively increased survival. In the same token this has also facilitated the emergence of other comorbidities, increasing the risk for drug interactions (DIs) and polypharmacy.The profile of these interactions, as well as their consequences in PLWH are still not completely elucidated. The objectives of this study included the description of the profile of these interactions, their prevalenceand their classification accordingly to the potential for significant or nonsignificant DIs. From June 2015 to July 2016, PLWH, on follow-up in an Infectious Diseases Referral Center in Belo Horizonte, Brazil have been investigated for the presence of DIs. A total of 304 patients were included and the majority (75%) had less than 50 years of age, were male (66.4%) and 37.8% were self-defined as brown skinned. Approximately 24% were on five or more medications and half of them presented with DIs. Patients older than 50 years had a higher frequency of ARV DIs with other drugs when compared to younger patients (p = 0.002). No relationship was found between the number of DIs and the effectiveness of ARV. As expected, the higher the number of non-HIV medications used (OR = 1.129 95%CI 1.004-1.209, p = 0.04) was associated with an increase in DIs. The high prevalence of DIs found and the data collected should be useful to establish measures of quaternary prevention and to increase the medication security for PLWH.